Perception of Foreign Tourists to Karawo Embroidery Handicrafts in Gorontalo Tourist Destinations - Lagalo, Anggraeni M. S; Usu, Nur Fadhlya (Journal of Asian Multicultural Research for Economy and Management Study, 2020)
The purpose of this study was focused on knowing the perceptions of tourists, both foreign tourists, about the craft of Karawo embroidery in Gorontalo Tourism Destinations. This research method using a quantitative approach itself is carried out using a questionnaire given to the public and tourists who visit the Karawo embroidery craft center. The sampling technique in this study used a non-probability or non-random sample selection technique. The results showed that the quantitative approach itself was carried out using a questionnaire given to the public and tourists who visited the Karawo embroidery craft center. The sampling technique in this study used a non-probability or non-random sample selection technique. The results of this study indicate that the Karawo embroidery craft has the potential to be developed as a tourist attraction in Gorontalo Province. Analysis of the attractiveness and perceptions of tourists who visit the Karawo embroidery craft center as well as the local community provide direction on the development of tourist attractions that are related to cultural aspects. The perception of foreign tourists in general gives a positive value to Karawo embroidery and argues that Karawo embroidery is unique from the manufacturing process and has its own characteristics with very beautiful motif designs.